Gestational Age Predicted by Femur Length in Bangladesh - Rashid, SQ (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Objective: Fetal femur length is an important parameter for determining gestational age. If we use tables based on Bangladeshi population, gestational age estimation will be more accurate. This study was therefore designed to determine the gestational age by fetal femur length measurement in our country. Methods: Healthy gravid patients with optimal dates were included in a prospective study. Fetal femur length along with other parameters was measured. A table and a graph were prepared by Polynomial regression model. Previously established nomograms were compared with it. Results: The gestational age predicted from the femur length measurements of 1223 subjects from 13 to 40 weeks are presented here in a tabulated form. Percentiles, mean and standard deviations were also derived. The quadratic model showed a good fit to the data. There was a gradual increase of the femur length measurements. From 13 to 27 weeks gestation, there was no clinically important difference between this and western nomograms for predicting gestational age but after 32 weeks the difference with western nomograms became significant. Conclusion: This nomogram is special for Bangladeshi population. It will give more accurate gestational age assessment than the western tables that are still followed in our country, especially in the 3rd trimester. Key Words: Gestational age; femur length; Bangladesh. DOI: 10.3329/jbcps.v28i3.6510 J Bangladesh Coll Phys Surg 2010; 28: 163-166